Preconcentration of Ion Ni(II) using Ca-Alginate Modified Resin with Dimethylglyoxime as a Filler Material of Column - Aman Sentosa Panggabean; Wirdhaningsih Wirdhaningsih; Subur P. Pasaribu (Jurnal Kimia Valensi, 2020)
The research about the preconcentration of Ni(II) ions using Ca-alginate resin modified with dimethylglyoxime (DMG) as a material filler of the column has been done. The stage of preconcentration done by using the water sample was passed through the column, then eluted using HNO3. The amount of Ni(II) in the eluate was measured using atomic absorption spectrophotometer (AAS). Several important parameters in the preconcentration stage have been studied. The optimal condition at the stage of preconcentration Ni(II) ions was retention at pH 4, the volume of sample was 10 mL, the volume of HNO3 eluent was 4 mL at a concentration of 1.5 M, with the retention of capacity value was 2.4657 mg Ni(II)/g resin. The analytical performance of this method is good, showed with repeatability value as a percentage of the coefficient of variance value was 4.06%, and can increase the limit detection of Ni(II) ions was 3.94 times if compared to direct measurements with AAS. The method can be applied to the determination of Ni(II) ions in the water samples from Mahakam river at port Samarinda with recovery percentage value was > 95 %, indicating that the matrix of samples did not affect the results of measurements.